Knowledge sharing culture in Malaysian Public Institution of higher education : an overview - Suhaimee, Sirajuddin; Abu Bakar, Ahmad Zaki; Alias, Rose Alinda (2006)
Knowledge sharing culture plays very important role in the successful implementation of Knowledge Management in any organization. A study has been conducted to explore the current status of Knowledge Sharing Culture among the Community of Practice in Malaysian Public Institution of Higher Education. Based on the questionnaire distributed to all 17 IT Managers in Malaysian PIHE, we found that the existence of Knowledge Sharing Culture in Malaysian PIHE still very low. Besides, this study came out with a proposal on how to motivate the Knowledge Sharing Culture in Malaysian PIHE.